Frasa Adjektiva dalam Bahasa Bolakme: Kajian Semantik - Yohanes Lose Dasilva; Febronius Densius Naja; Amelia Kaisiepo; Sutarman Borean (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This research aims to analyze adjectival phrases in the Bolakme language from a semantic perspective. The main focus of this research is on the form, structure, and meaning of adjectival phrases, as well as their comparison with equivalents in Indonesian to reveal the distinctive nuances of meaning in the Bolakme language. This research uses a descriptive qualitative approach, with data sources consisting of 30 adjectival phrases obtained through interviews, direct observation, and documentation. The sample was taken using purposive sampling with a total of 10 native Bolakme speakers as informants. The analysis technique uses meaning and context analysis methods. The research results show that adjectival phrases in the Bolakme language have a wealth of forms and meanings. Some phrases are formed by the repetition of morphemes to emphasize meaning, such as arek-arek which means